(untitled) (Czech Journal of International Relations, 1995)
Karl Kaiser and Hanns W. Maull (eds.): Germany’s New Foreign Policy. Volume 1 - Foundations. Research Institute of the German Society for Foreign Policy. R. Oldenbourg Verlag, Munich 1994, 206 + XXV pages, ISBN 3-486-56064-6.